SnS2/Bi4Ti3O12 Heterostructure Material: A UV‐Visible Light Active Direct Z‐Scheme Photocatalyst for Aqueous Phase Degradation of Diazinon. Issue 4 (30th January 2020) - Das, Krishnendu; Majhi, Dibyananda; Bariki, Ranjit; Mishra, Braja G.
Abstract: In this study, a series of Z‐scheme SnS2 /Bi4 Ti3 O12 heterostructure photocatalyst materials were synthesized by a two‐step process. Initially, Bi4 Ti3 O12 (BT) nanopellets with planar dimension of 350–400 nm were prepared by a facile combustion synthesis route. The SnS2 nanoparticles (10–20 nm) were subsequently decorated over BT surface using a hydrothermal method. The heterostrucure materials possess orthorhombic BT and hexagonal SnS2 crystalline phases with high interfacial contact and strong interaction at microscopic level. Optical and photoelectrochemical (PEC) measurements suggest improved UV‐visible light absorption and enhanced charge carrier separation and migration properties. The SnS2 /Bi4 Ti3 O12 materials displayed excellent photocatalytic activity for degradation of diazinon insecticide (>90 % with kapp ∼0.019 min −1 ) in aqueous media under UV‐visible light illumination. The valence band (VB) holes and OH radicals were identified as major transient species responsible for photodegradation of diazinon. A Z‐scheme electron transfer process has been proposed to explain adequately the generation of these radicals which was deduced from PEC measurements, scavenger and radical trapping experiments. Mechanistic study revealed that diazinon degradation occured in a series of steps to produce 2‐isopropyl‐6‐methyl‐pyrimidin‐4‐ol as a major intermediate which was further mineralized over the photocatalyst surface. The process potential of the developed photocatalytic method has been tested for different water matrices and interfering anionic species with radical quenching activity. Abstract : A sustainable photocatalytic degradation route is developed for mineralization of diazinon insecticide from aqueous sources using SnS2 /Bi4 Ti3 O12 heterostructure materials as photocatalyst under visible light irradiation. The photocatalyst operates through a direct Z‐scheme electron transfer mechanism to generate highly reactive . OH and O2 . – radicals responsible for diazinon photodegradation.